UNLEASHING THE POWER OF CML THE JOURNEY TO EKSA AWARD - Fathiah Izzati, Mohammad Fadzillah; Hanisah, Kasbon (Pusat Bahasa Moden (PBM), 2024)
21 February 2024 - The Public Sector Conducive Ecosystem, better known as EKSA, is a rebranding exercise of Public Sector 5S practice. The initiative aims to strengthen the organisational culture of high performance and innovation among public sector agencies by providing a conducive environment, work culture, and positive values for public servants. In the spirit of EKSA, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), is also implementing this practice to meet its objectives. In preparation for the upcoming Internal Audit on February 29th for the EKSA Award, which coincides with Hari Kualiti dan Inovasi 2024, the CML family joined hands for a gotong-royong to clean and organise the central administrative office in Pekan.